Forced feeding of convicts: problems of theory and practice (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The problematic issues of legislative consolidation and application of forced feeding to convicts who refuse to take food in institutions of execution of punishment are considered.An analysis of domestic and international legislation in the field of treatment of convicts, prohibition of torture and other cruel, inhuman or degrading treatment and punishment, principles of medical ethics and deontology regarding the admissibility of forced feeding of persons who have declared a hunger strike was carried out.Special attention is paid to the analysis of the decisions of the European Court of Human Rights against Ukraine, which found a violation of Article 3 of the Convention on the Protection of Human Rights and Fundamental Freedoms in the context of the treatment of convicts during their forced feeding, which was classified as torture.Emphasis has been placed on the fact that the Convention on the Protection of Human Rights and Fundamental Freedoms in itself does not prohibit forced feeding, the purpose of which is to save the life of a specific person who is in custody and who deliberately refuses to eat. At the same time, it has been emphasized the need to comply with the requirements established by the European Court of Human Rights regarding the implementation of this procedure.It has been proposed to abandon and prohibit the forced feeding of a mentally healthy and capable person who has declared a hunger strike, contrary to his informed and voluntary refusal, in the form in which it currently exists, replacing it with artificial feeding (supportive therapy) with the express or necessarily implied consent of the person.